THE ROLE OF FISHERMEN IN ASSISTING MARITIME LAW ENFORCEMENT AGENCIES TO PREVENT MARITIME SECURITY THREATS - Nasution, Anta Maulana (Jurnal Pertahanan dan Bela Negara, 2018)
Abstract – Indonesia’s sea is approximately 2/3 wider than the mainland, with very strategic geographical posisition located at the cross point of Indian and Pacific Oceans. This geographical posisition serves as strategic route for shipping, with every shipment from the west to east and the opposite will sail through the Indonesian sea. This can be both opportunity or challenge, depending on how Indonesia will manage it. If the State did not manage it well, it will increase the maritime security threats, such as IUU fishing, smuggling, and piracy. These threats may seriously disrupt the marine economics development, given the limited number of armaments and personnel of marine law enforcement agencies. Therefore, the capacity of fishermen in assisting marine law enforcement agencies to prevent the maritime security threat is inevitable. This study uses descriptive qualitative method. There are two types of data sources, primary and secondary data sources. Primary sources is obtained through interview with stakeholders and fishermen organization, while secondary data source is obtained by literature study. The role of fishermen in assisting maritime law enforcement agencies, in this case PSDKP KKP and Navy, to prevent maritime security threats is prescribed role or recommended role. The prescribed role is shown by the community group program established by PSDKP and Coastal Development in Rural area which is established by the Navy. With this program, the fishermen can supply informations about maritime security threats to PSDKP and the Navy so that they can act immediately to prevent these threats. Keywords: Maritime Security Threats, Fishermen, Community Group Supervisor (Pokmaswas), Development Of Coastal In Rural Area (Bindesir)